THE MISTAKE BUSTER TECHNIQUE TO IMPROVE LOWER SECONDARY STUDENTS’ GRAMMAR MASTERY OF TENSES - Muthyaningsih Rahmadhani; Muh. Yusuf; Mujahidah; Nur Asiza (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aims to examine the effectiveness of the Mistake Buster Technique in improving lower secondary EFL students’ grammar mastery, particularly in the use of the simple present tense, present continuous tense, simple past tense, and past continuous tense. This research employed a quantitative method with a pre-experimental design using a one-group pre-test and post-test model. The sample consisted of 19 eighth-grade students of MTs DDI Kanang selected through purposive sampling. The data were collected through a grammar test administered before and after the treatment. During the treatment, students were guided to identify, analyze, and correct grammatical errors individually and collaboratively. The data were analyzed using descriptive statistics, a normality test, and a paired sample t-test. The findings showed that the students’ mean score increased from 53.947 in the pre-test to 70.921 in the post-test. The paired sample t-test result showed a significance value of 0.00, which was lower than 0.05, indicating a significant difference between the students’ grammar mastery before and after the treatment. These results indicate that the Mistake Buster Technique was effective in improving students’ grammar mastery. The study implies that error-based and student-centered grammar instruction can help students become more active, reflective, and aware of grammatical rules, especially in learning basic English tenses.